Feedback control of thermocapillary convection in a rotating fluid layer with free-slip bottom - Ishak Hashim; Zailan Siri (Universiti Kebangsaan Malaysia, 2009)
The linear stability theory is applied to investigate the effects of rotation and feedback control on the onset of steady and oscillatory thermocapillary convection in a horizontal fluid layer heated from below with a free-slip bottom. The thresholds and codimension-2 points for the onset of steady and oscillatory convection are determined. The effect of Pr – Ta parameter space dividing the steady and oscillatory convection regions is demonstrated.